2004
DOI: 10.1159/000079417
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Cerebral Perfusion Decrease in Mild Alzheimer’s Disease Revealed by SPECT with Statistical Parametric Mapping Method

Abstract: Fifteen patients with mild Alzheimer’s disease received baseline and follow-up technetium-99m hexamethylpropylene amine oxime SPECT examinations paired with neuropsychological assessments, including the Cognitive Ability Screening Instruments (CASI). The differences between baseline and follow-up SPECT images were analyzed by the voxel-based paired t test of the statistical parametric mapping technique. A simple regression analysis was also conducted to analyze the correlation between CASI sub-scores and both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Fourteen studies, 20–23,50,52–60 including 21 patient (sub)groups, reported on longitudinal changes in rCBF in smaller brain regions (Table 3), such as specific gyri that have been associated with AD pathology. Although longitudinal increases in rCBF have been rarely observed, two studies found an increase in the postcentral gyrus 20,59 .…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen studies, 20–23,50,52–60 including 21 patient (sub)groups, reported on longitudinal changes in rCBF in smaller brain regions (Table 3), such as specific gyri that have been associated with AD pathology. Although longitudinal increases in rCBF have been rarely observed, two studies found an increase in the postcentral gyrus 20,59 .…”
Section: Methods and Resultsmentioning
confidence: 99%
“…For consensus, disagreements were resolved by discussion and/or by consulting a third reviewer (JC). Eventually, 20 studies [19][20][21][22][23][24][47][48][49][50][51][52][53][54][55][56][57][58][59][60] were included in this systematic review, including five studies [19][20][21][22][23] eligible for quantitative synthesis. A flowchart of the study identification and selection process can be found in Figure 1.…”
Section: Eligibility Criteria and Study Selectionmentioning
confidence: 99%